Morphometric Analysis of Foramen Magnum for Sex Determination in South Indian Population - K., Radhakrishna S.; H., Shivarama C.; A., Ramakrishna; B., Bhagya (Journal of Health and Allied Sciences NU, 2012)
In this study the foramen magnum was analyzed for sex differences using standard osteometric techniques.We analyzed 100 (55 males and 45 females) skulls from the department of Anatomy, Yenepoya Medical College which were in good condition with a record of sex. The cranial base was visually assessed for foramen magnum shape. Morphometry (anteroposterior diameter (APD)& Transverse diameter (TD)) was determined and their differences by gender (p <0.05) were ascertained.Oval shape was the most common followed by round, tetragonal and pentagonal in both sex. The results demonstrated that sexual dimorphism is present in the foramen magnum. APD and TD were higher in male skulls than females (34.04 vs 31.72 and 28.63 vs 26.59).In incomplete skeletons, metric analysis of the foramen magnum may provide a statistically useful indication as to sex of the unknown skull.
Keywords: foramen magnum; shape; anterioposterior diameter; transverse diameter; sexual dimorphism